Evaluating Antioxidant Eugenol on Oxidation Stability of Biodiesel Synthesized from Used Frying Oil - de Souza, Eliane Ferreira; Ramos, Talita Cuenca Pina Moreira; Simionatto, Euclesio; Cavalheiro, Alberto Adriano; Fiorucci, Antonio Rogério; da Silva, Margarete Soares (Orbital: The Electronic Journal of Chemistry, 2018)
Due the environmental appeal, the demand of new processes and inputs has been increasing considerably in the last decade. Biodiesel is a biodegradable fuel obtained from vegetable oils or animal fats, including those discarded after use. The methyl and ethyl transesterification routes for biodiesel production were tested by using residual frying oil as raw material through the homogeneous basic catalyst, such as sodium hydroxide. In present work, it was evaluated the efficiency of the eugenol on the oxidation stability of the methyl and ethyl biodiesels synthesized from residual frying oil. The chromatographic analysis determined that the conversion of the yield to the methyl and ethylic esters (biodiesel) was 90.6 % and 87.3 %(m/m) respectively. For both biodiesel samples a rise of the eugenol concentration added resulted in an increase of the induction period (oxidation stability parameter evaluated by Rancimat method), with a consequent reduction of the acid number. Taking these results into account, it can be concluded that the samples obtained after eugenol addition can be used as biodiesel. DOI: http://dx.doi.org/10.17807/orbital.v10i1.1030